Identification of the Microstructure of TMT rebars and its impact on Mechanical properties (OODBODHAN, 2025)
Steel is essential to industrial progress, and understanding its heat treatment processes is crucial for material optimization. This study investigates the microstructure of TMT rebars under various heat treatments (annealing, normalizing, quenching) and their impact on mechanical properties such as ductility, hardness, and strength. Microscopic observations reveal phase transformations such as ferrite, pearlite and martensite, and their relationship with mechanical performance is examined. The Hall-Petch equation is applied to determine the mechanical strength of the steels. Samples were observed under a 500x magnification microscope after polishing and etching to expose microstructural structure. In annealed TMT rebars, the individual size of ferrite increases, resulting in increased ductility. Finer grains observed at lower temperatures lead to higher hardness, whereas coarse grains observed at higher temperatures lead to better machinability of TMT rebars. Similar to annealing, in the normalization process of TMT rebars, as the temperature rises, the grain structure becomes fine-to-coarse. Quenched steel is characterized by the formation of martensite, which signifies high hardness, strength, and brittleness. These results show how important heat treatment is in determining a material's characteristics. Different factors, such as cooling rate, heat treatment method, and material composition, impact our understanding of steel's properties.